Mechanical Behavior Analysis of a Friction Stir Welding (FSW) for Welded Joint Applied to Polymer Materials (Fracture and Structural Integrity, 2018)
Welding is a technique of fusion joining the material involving a process of inter-molecular diffusion adhesion. Polymer welding is an assembly method among several known assembly techniques such as gluing. This welding process applies to thermoplastics; they have the rheological or softening characteristics during melting. This process is fast and controlled in order to obtain a solid and durable mechanical connection on the series parts. This study focuses on the weldability of high density polyethylene (HDPE) using the friction stir welding technique. A parametric choice was made to optimize the operating parameters namely the shape of the welding tool, the speed of rotation and the speed of advance of the tool.  Monotonic tensile tests were used to compare the mechanical characteristics between a HDPE test specimen and a specimen taken from an FSW weldment.It emerges from this study that the FSW welding introduces a weakening of the joints characterized by a clear decrease of the deformation at break.
Keywords: Welding; Polymer; Tensile test; FSW; Vickers hardness test